'Torn, wrinckled, stained, and otherwise naughty sheets'. How should we interpret paper faults in seventeenth century paper? - Honey, A (Institute of Conservation Book and Paper Group, 2020)
Conservators are routinely faced with torn, damaged or wrinkled papers in their work and the types of damage found may seem unremarkable. However, a surprisingly large number of flaws and faults found in early paper were made during manufacture rather than in later use. Recent conservation work to one of the Bodleian Library’s two copies of the First Folio, the 1623 first publication of William Shakespeare’s (1564–1616) collected drama, has led to research of these faults and a new appreciation of them.